Putting on the Armour: A Response to Richard Utz - Matthews, David (2021)
There was a time not all that long ago when what is now known as medievalism was largely disregarded, so I take it as a mark of distinction to have my book Medievalism: A Critical History scrutinised as closely as it has been and given such generous attention by Richard Utz. As a still somewhat inchoate field, medievalism is still a volatile and changeable one. The following remarks are offered more in the spirit of keeping a critical conversation going within that context, than out of any desire to correct or to “get it right”.